Paglalayag - Gomez, Michaela Cecilia Norberte; Tiongson, Nicanor G. (2012)
"The OFW phenomenon has been a part of Philippine society. One popular form of overseas work for most Filipinos is seafaring. Paglalayag is a documentary that takes a look at the lives of a young and an old seafarer. The film explores the subjects' motivations in pursuing their careers as well as the effects that their profession has had on their personal lives. The goal of the documentary is to bring about the contrasting ideas about working overseas. It aims to ask the question if it is still wirth it. A portion of the documentary was shot onboard the DHL Pacific that sailed from China to Australia. The Filmmaker sent her camera to the crew onboard and gave directions via Internet and phone. Footage was sent to the filmmaker whenever possible. The subjects were then shot and interviewed by the filmmaker when they came home."
Vita.
Undergaduate thesis (A.B. Film and Audio Visual Communication)--Univesity of the philippines, Diliman.
Keywords: Paglalayag (Sort films); Documentary films -- Philippines